2011
DOI: 10.1177/1559827611425762
|View full text |Cite
|
Sign up to set email alerts
|

Health Implications of a Vegetarian Diet

Abstract: There is now a significant amount of research that demonstrates the health benefits of vegetarian and plant-based diets, which have been associated with a reduced risk of obesity, diabetes, heart disease, and some types of cancer as well as increased longevity. Vegetarian diets are typically lower in fat, particularly saturated fat, and higher in dietary fiber. They are also likely to include more whole grains, legumes, nuts, and soy protein, and together with the absence of red meat, this type of eating plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 182 publications
3
69
0
9
Order By: Relevance
“…Diets high in whole-plant foods and low in red and processed meat may provide benefits for the prevention and treatment of not only obesity but other chronic health problems, including type 2 diabetes and CVD. 26 Plant foods are rich in fibre and a range of phytochemicals and antioxidants that are believed to confer these aforementioned health benefits. 26 As population surveys show that women tend to eat more fruit and vegetables than men, while men's diets tend to be higher in red and processed meats and lower in fibre, 27 there is greater scope for men's diets to include more plant foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets high in whole-plant foods and low in red and processed meat may provide benefits for the prevention and treatment of not only obesity but other chronic health problems, including type 2 diabetes and CVD. 26 Plant foods are rich in fibre and a range of phytochemicals and antioxidants that are believed to confer these aforementioned health benefits. 26 As population surveys show that women tend to eat more fruit and vegetables than men, while men's diets tend to be higher in red and processed meats and lower in fibre, 27 there is greater scope for men's diets to include more plant foods.…”
Section: Discussionmentioning
confidence: 99%
“…26 Plant foods are rich in fibre and a range of phytochemicals and antioxidants that are believed to confer these aforementioned health benefits. 26 As population surveys show that women tend to eat more fruit and vegetables than men, while men's diets tend to be higher in red and processed meats and lower in fibre, 27 there is greater scope for men's diets to include more plant foods. Furthermore, the benefit of the greater muscle mass of men also means they have a greater requirement for dietary energy than women, through greater intakes of food.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetarianos tendem a ser mais magros que onívoros, em parte poderia ser pelo alto consumo de fibras (9) . Resultados reforçam que, dietas vegetarianas parecem ter benefícios para perda de peso comparadas com dieta de onívoros (13) . As variáveis metabólicas, glicemia e perfil lipídico, assim como pressão arterial, não foram diferentes entre grupos, mas ambos apresentavam, na maior parte, resultados adequados de acordo com referências.…”
Section: Introductionunclassified
“…In fact, in Western countries, a vegetarian diet may present a significant advantage over meat-based diets, and a number of studies have shown increased longevity in vegetarians (Marsh, Zeuschner, & Saunders, 2012;Key, Fraser, Thorogood, et al, 1999;Key, Thorogood, Appleby, & Burr, 1996).…”
Section: Risk Factors Of Vegetarians V Non-vegetariansmentioning
confidence: 99%
“…The research does demonstrate that vegetarians and vegans have lower rates of a number of health problems, including obesity, hypertension, type 2 diabetes, some cancers, gallstones, kidney stones, constipation, and diverticular disease (Marsh, Zeuschner, & Saunders, 2012;Leitzmann, 2005;Segasothy & Phillips, 1999). In fact, in Western countries, a vegetarian diet may present a significant advantage over meat-based diets, and a number of studies have shown increased longevity in vegetarians (Marsh, Zeuschner, & Saunders, 2012;Key, Fraser, Thorogood, et al, 1999;Key, Thorogood, Appleby, & Burr, 1996).…”
Section: Risk Factors Of Vegetarians V Non-vegetariansmentioning
confidence: 99%